DAMPAK KEGIATAN OBJEK WISATA MONPERA KOTA PALEMBANG TERHADAP LALU LINTAS SEKITARNYA - Hardiansyah, Dani; Muhammad Aminuddin, Kiagus; Sutejo, Yulindasari; Ramadhani, Ramadhani (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2024)
One of the issues in road infrastructure is traffic congestion, which leads to longer travel times for road users. Traffic congestion is a serious problem in big cities like Palembang, including around Monpera, a tourist attraction located near the city center surrounded by busy roads. Traffic involves variables such as volume, speed, and density with random variations. Therefore, it is important to study the impact of Monpera's tourism activities on traffic. The research methodology used includes surveys and observations to gather data on visitor numbers, air quality testing, and traffic volume during peak hours. The research findings indicate that the impact observed is an increase in traffic volume, especially on weekends from 8:00 AM to 12:00 PM. Based on air quality measurements around Monpera, it still meets the established environmental standards. This suggests that Monpera's activities do not have significant effects on air quality. However, the level of traffic service in this area is rated low at 0.77 indicating that traffic flow tends to be unstable